Branded! a visual semiotic analysis on how NCCC communicates their brand identity through print ads - Puyod, Stephanie Victoria J.
Advertisement contribute significantly to showing and shaping a company's brand and image. This study, branded! A visual semiotic analysis on how NCCC communicates their brand identity through print ads, is a content analysis on fifty image and print promo advertisements of the retail chain. New City Commercial Corporation (NCCC). The researcher conducted an initial corporate background study which helped in determining the branding strategies (market segment, position and audience approach) set by the company. The subsequent main ad content analysis then reveals how the company presents such market objectives through the print advertising medium. By noting the general themes regarding the ads' textual and visual content, the researcher was able to discern how the materials mainly featured benefits and urgency factors to attract and influence its audiences. Associative terms and word play techniques serve an important role in capturing the public's interest, highlighting these factors and creatively communicating the company's brand position. These are more emphasized and established through the ads' eye-catching and recurring visual elements, like large typeface, red fonts and radial lines. Furthermore, as the ads were evaluated and compared with NCCC's actual market objectives this study reveals that the company's corporate brand identity is relatively consistent with its cost-efficient, complete, caring and fun image projection.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media Arts